Repetition Values on Martin Luther King Jr. Speech: Nilai Pengulangan pada Pidato Martin Luther King Jr. - Ihsan, Mas Darul (JEES (Journal of English Educators Society), 2018)
There are so many speeches delivered by such famous people in this world. But, if we are asked to give the point of view about the impact of each speech delivered then the speech from Martin Luther King Jr. will convey the high meaning in term of rethorical speech especially the content and the context about the concepts of repetition found. The speech was on 28th of August 1963, at the Lincoln Memorial, Washington D.C in a verbal ways and its text become the secondary data to be analyzed with much focus on emphasizing phrases, words or sentences. By using the concept of rethoric perspective through repetition such as anaphora, epistrophe and epizeuzis, the researcher wants to know the values behind the repetition. That is why, the analysis is using the descriptive qualitative research on taking the secondary data that has been adapted from the video and the text of the speech itself. The conclusion especially on the ideas of repetition are that Martin Luther King Jr. tries to make sure his audiences about that 1) the repetition is something more that the meaning itself, it is above. 2) The struggle, it is something true, needs to be realized in the real life, and adds the weight of the expection to be equal and free.